A column of one's own: putting women on the pages of the RAPI Journal, 1977–1982. Issue 1 (2nd January 2017) - Grant-Smith, Deanna; Osborne, Natalie
ABSTRACT: Between 1977 and 1982, the Royal Australian Planning Institute (RAPI) Journal, the forebear of Australian Planner, featured a column dedicated to women and planning. The column, entitled Marion, sought to raise awareness, exchange information and stimulate discussion about issues relating to women and planning. The column highlighted discriminatory employment and planning practices including the absence of women in senior planning positions. It also considered issues associated with planning for women and the impact of planning on women's lives, particularly from an intersectional and international perspective. A clear link was made between the need for women in planning at all levels to undertake planning for and with women. Grounded in the gains made by the feminist movement, the column championed the unique needs of women in urban design and planning but situated these within the broader social challenges experienced by women around their lack of access to power, resources, education and decision-making. In this article, we use Virginia Woolf's feminist text, A Room of One's Own, as a hermeneutical device for reviewing the Marion column, reflecting on the place of women in the pages of the journal of the RAPI Journal and in the planning profession, and documenting its legacy.